2015
DOI: 10.1186/s40249-015-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal opportunistic parasites infections in the University hospital of Bobo-Dioulasso, Burkina Faso

Abstract: BackgroundGastrointestinal parasites infections are widespread in Africa and their prevalence infections vary from country to country. This study aimed at assessing the prevalence of opportunistic intestinal parasites infection and other gastrointestinal parasites infection among patients attending the laboratory of Parasitology and Mycology of the University Hospital Souro Sanou of Bobo-Dioulasso.MethodsA hospital cross-sectional based study was conducted from April to August, 2012. Participants were persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
2
22
3
1
Order By: Relevance
“…We found that 25.0% of the patients in our study were infected with C. belli. This rate is high compared to levels noted in most of the recent reports from Sub-Saharan Africa, indicating a prevalence of 0.7% in the general population of Burkina Faso and Mozambique ( Cerveja et al., 2017 ; Sangare et al., 2015 ) and 3.5%–10% in HIV patients in Nigeria and Cameroon respectively ( Olusegun et al., 2009 ; Vouking et al., 2014 ). Remarkably, in our study no differences in number of positive cases were seen between patients with or without ART provided, which would have been expected.…”
Section: Discussionmentioning
confidence: 66%
“…We found that 25.0% of the patients in our study were infected with C. belli. This rate is high compared to levels noted in most of the recent reports from Sub-Saharan Africa, indicating a prevalence of 0.7% in the general population of Burkina Faso and Mozambique ( Cerveja et al., 2017 ; Sangare et al., 2015 ) and 3.5%–10% in HIV patients in Nigeria and Cameroon respectively ( Olusegun et al., 2009 ; Vouking et al., 2014 ). Remarkably, in our study no differences in number of positive cases were seen between patients with or without ART provided, which would have been expected.…”
Section: Discussionmentioning
confidence: 66%
“…The community-based accelerated expansion of health facilities in Ethiopia being operational since 2004 seems ineffective as a sound reduction in the prevalence of such neglected diseases was expected. Parts of communities in other low-income countries such as India (43-49%) [12,38], Nepal (52-59%) [39,40], Nigeria (58.3-81%) [15,41,42], Burkina Faso (65-84.7%) [13,43], and Peru (100%) [16] are also reported to be at high-risk of IPIs indicating that IPIs continue to be major threats to poor society. Low socioeconomic status, low educational level, and hence poor knowledge, attitude, and practices towards easily preventable disease, poor personal hygiene, and environmental sanitation, lack of potable, and sufficient drinking water are the most important risk factors for the high infection rate of intestinal parasites among poor communities.…”
Section: Discussionmentioning
confidence: 99%
“…positive/No. tested)Diagnostic techniqueGenotyping(target gene)ReferenceAlgeriaPatients with digestive disorders≤ 80 years3.6% (38/1042)0.1% (1/1042)Direct wet mount, formal ether concentration, iodine solution and acid fast stainingNot genotyped[271]AlgeriaSporadic cases≤ 75 years41.7% (25/542)Iodine stainingNot genotyped[272]AngolaChildren (with and without diarrhoea)≤ 12 years0.1% (44/328); 21.6% (73/338)30.0% (101/337)Iodine and acid fast staining, and immunoassayNot genotyped[273, 274]BotswanaChildren with diarrhoea< 5 years60.0% (45/75)Not statedNot genotyped[41]Burkina FasoPatients with diarrhoeaAll ages26.5% (77/291)Acid fast stainingNot genotyped[275]CameroonIndividuals from Nloh and Bawa villagesNot specified7.1% (14/197)1.5% (3/194)ImmunoassayNot genotyped[276]CameroonHIV/AIDS-positive and negative individuals15–70 years0.3% (1/396)2.5% (10/396); 6.0% (12/200); 14.4% (46/320)Direct microscopy, formal ether concentration, iodine and acid fast stainingNot genotyped[277279]Central Africa RepublicEmployees at Dzanga-Sangha ParkNot specified2.1% (1/48)PCR tpi [122]Central African RepublicChildren (with and without diarrhoea)Not stated; < 5 years15.6% (27/173); 4.4% (29/666)10.4% (18/173); 7.7% (51/666)Merthiolate iodine formaldehyde concentration, acid fast staining, immunoassay and multiplex PCRNot genotyped[29, 280]ChadIndividuals from different regions≤ 76 years3.5% (16/462)Merthiolate-iodine-formaldehyde concentrationNot genotyped[281]ChadEuropean military UN peace keepers…”
Section: Diagnosis and Prevalence Of Cryptosporidium And Giardia In Amentioning
confidence: 99%